Application of Dot-Immunoassay for Detection of Plague Agent Antigens in the Field Samples - O. A. Noskova; T. Yu. Zagoskina; E. N. Subycheva; E. Yu. Markov; Yu. O. Popova; L. G. Gridneva; E. P. Mikhailov (Проблемы особо опасных инфекций, 2014)
CFU/ml) and soluble antigens (FI) − ≥ 4.8 ng/ml and high specificity, confirmed by the absence of false-positive reactions with five heterologous microorganisms. The test-systems were used for Y. pestis antigen detection in field material from the territory of the Altai mountain natural plague focus by dot-immunoassay with comparison of the received results in passive hemagglutination reaction. Test-systems possessed a number of advantages as compared to routine serological reactions and could be applied with success by practical public health services both in stationary and field conditions.